An improved electromagnetism-like algorithm for numerical optimization - Tan J.-D.; Dahari M.; Koh S.-P.; Koay Y.-Y.; Abed I.-A. (Elsevier B.V., 2023)
Algorithms; Benchmarking; Global optimization; Iterative methods; Nonlinear equations; Probes; Bench-mark problems; Computational simulation; Electromagnetism-like algorithm; Electromagnetism-like mechanism algorithms; Electromagnetism-like mechanisms; Metaheuristic; Numerical optimizations; Split-Probe-Compare; Optimization